CCR6 Deficiency Impairs IgA Production and Dysregulates Antimicrobial Peptide Production, Altering the Intestinal Flora - Lin, Ya-Lin; Ip, Peng-Peng; Liao, Fang (Frontiers in Immunology, 2017)
Intestinal immunity exists as a complex relationship among immune cells, epithelial cells and microbiota. CCR6 and its ligand-CCL20 are highly expressed in intestinal mucosal tissues, such as Peyer’s patches and isolated lymphoid follicles. In this study, we investigated the role of the CCR6-CCL20 axis in intestinal immunity under homeostatic conditions. CCR6 deficiency intrinsically affects germinal center reactions in Peyer’s patches, leading to impairments in IgA class switching, IgA affinity, and IgA memory B cell production and positioning in Peyer’s patches, suggesting an important role for CCR6 in T-cell-dependent IgA generation. CCR6 deficiency impairs the maturation of isolated lymphoid follicles. In these follicles, group 3 innate lymphoid cells are important components and a major source of IL-22, which stimulates intestinal epithelial cells to produce antimicrobial peptides. We found that CCR6 deficiency reduces IL-22 production, likely due to diminished numbers of group 3 innate lymphoid cells within small-sized isolated lymphoid follicles. The reduced IL-22 levels subsequently decrease the production of antimicrobial peptides, suggesting a critical role for CCR6 in innate intestinal immunity. Finally, we found that CCR6 deficiency impairs the production of IgA and antimicrobial peptides, leading to increased levels of Alcaligenes in Peyer’s patches and segmented filamentous bacteria in intestinal epithelial cells. Thus, the CCR6-CCL20 axis plays a crucial role in maintaining intestinal symbiosis by limiting the overgrowth of mucosa-associated commensal bacteria.